CONFORMITY IN DISTRICT LOCATION MINIMARKET BABAKAN CIPARAY BANDUNG - Sahbanriah, Dewi Nur (2013)
Minimarket is a modern retail which is currently undergoing a fairly rapid growth. This is supported by the current consumption patterns that can be said at this stage of the transition, that from traditional retailing to modern retailing. The problems that exist in the District BabakanCiparay is minimarket establishment that does not take into considerations minimarket location determination and establishment of Bandung Regulation No. 2 of 2009 on Structuring Traditional Markets, Shopping Centers and Stores Modern minimarket making uncontrolled growth, threatening the existence of small merchants are nearby. Therefore formulation of the issues raised in this research is: (1) How does the pattern of distribution of BabakanCiparay minimarket in Bandung district, (2) How suitability minimarket in BabakanCiparay Bandung District in conjunction with demographic, land use, traffic and accessibility and radius minimarket services, (3) What is the impact of the existence of small traders minimarket surrounding. The method used is descriptive method. The research variables are indicators of the location of the study are (1) the distribution minimarket; (2) suitability minimarket, (3) the negative impact on small traders. Population of that region throughout the region contained in the District BabakanCiparay minimarket and human population is scattered in small merchant BabakanCiparay District. For the sample selected areas Margasuka Village, Village Sukahaji, Village Margahayu, Babakan Village, and the Village BabakanCiparay while for the sample was 30 social small traders. Then do the retrieval of data by distributing questionnaires. The data analysis technique used is R Scale analysis, GIS analysis and percentage analysis. Based on the survey results revealed that the minimarket in the District BabakanCiparay have scattered distribution pattern is uneven. Minimarket in District BabakanCiparay which have compatibility with criteria such as location minimarket domografi, land use, traffic, and accessibility, and service radius is a mini-A (Indomart), F (Alpamart), H (Yomart), I (Ananda), J (GemaTasik), K (Indomart) and L (Alpamart). Minimarket has a negative impact on existence of small traders around it because of a decline in revenue, number of customers, types of goods, and the volume of goods each day. Conclusion that there is still a minimarket in District BabakanCiparay are not taking into consideration the location of mini-determination and the establishment of Bandung Regulation No. 2 of 2009. This should be a consideration in the local government granted permission for the establishment of a minimarket can impact existence of traders around it Keywords: Location, Suitability, Minimarket